Peer Education Innovation: Strengthening Peer Educators in the Nasyiatul Aisyiyah Adolescent Posyandu Programme - Fitriyani Fitri; Leila Nisya Ayuanda; Windha Widyastuti; Ana Ayu Zulfa; Arifa Maulida (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Adolescent reproductive health is a serious issue with long-term and complex impacts. One inhibiting factor is the lack of peer educators, even though peer-to-peer approaches have proven effective in improving adolescent health knowledge and behavior. Nasyiatul Aisyiyah (NA), as a youth organization, plays a crucial role in improving public health, particularly in the area of ​​adolescent reproductive health, by involving its members as peer educators. The peer educator training method included explaining material on adolescent reproductive health, practicing adolescent nutritional status screening, and practicing yoga as a physical activity that can support adolescent health. The results of this activity demonstrated an increase in the knowledge, motivation, and skills of PASHMINA members in the field of reproductive health. Furthermore, this activity successfully formed trained PASHMINA members who are ready to serve as peer educators in their communities. The active role of peer educators is expected to have a positive impact on improving adolescent reproductive health in Pekalongan and building greater awareness among adolescents regarding the importance of maintaining reproductive health.